1997
DOI: 10.1002/j.2161-1912.1997.tb00324.x
|View full text |Cite
|
Sign up to set email alerts
|

Counseling Mexican American Seniors: An Overview

Abstract: This article examines assessment and counseling techniques that correspond to the sociocultural framework of Mexican American seniors. Acculturation. familial, and adaptation themes are delineated for ensuring appropriate interventions. Case vignettes elucidate these perspectives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Sue et al (1982) described this approach to cultural competence using a now widely recognized tripartite model calling for increased practitioner awareness, knowledge, and skills. This individual focus led to a wealth of work intended to provide practitioners with information they needed to provide services to members of specific minority communities (Applewhite, 1998;Diller, 2004;Hays, 2001;HHS, 2001;Sue & Sue, 2003;Thomason, 1991;Zuniga, 1997). The awareness, knowledge, and skills approach to cultural competence seeks to impart culturally specific interpersonal skills and increase knowledge of specific cultural artifacts that will facilitate communication and, consequently, improve the consistency of behavioral health outcomes among persons from different cultural backgrounds.…”
mentioning
confidence: 99%
“…Sue et al (1982) described this approach to cultural competence using a now widely recognized tripartite model calling for increased practitioner awareness, knowledge, and skills. This individual focus led to a wealth of work intended to provide practitioners with information they needed to provide services to members of specific minority communities (Applewhite, 1998;Diller, 2004;Hays, 2001;HHS, 2001;Sue & Sue, 2003;Thomason, 1991;Zuniga, 1997). The awareness, knowledge, and skills approach to cultural competence seeks to impart culturally specific interpersonal skills and increase knowledge of specific cultural artifacts that will facilitate communication and, consequently, improve the consistency of behavioral health outcomes among persons from different cultural backgrounds.…”
mentioning
confidence: 99%
“…Research has demonstrated clear differences in attitudes and behaviors among cultural groups (Blevins & Papadatou, 2006) related to issues such as advance directives and support for "assisted suicide" and euthanasia (Werth, Blevins, et al, 2002). Some of the counseling literature has addressed cultural concerns near the end of life, including articles on members of different ethnic groups in the United States (Inman, Yeh, Madan-Bahel, & Nath, 2007;Safonte-Strumolo & Dunn, 2000;Shimabukuro et al, 1999;Zuniga, 1997).…”
Section: A9c Confidentialitymentioning
confidence: 99%
“…Through applying a strengths perspective they represent countless opportunities for social workers to combine the elements of direct clinical work and social action. The strengths perspective, as a new model for social work intervention, has been successfully introduced into individual and family change efforts to address significant social problems such as homelessness (Banerjee, 1997;Boes and van Wormer, 1997;Thrasher and Mowbray, 1995), provide support to families (Early and GlenMaye, 2000;Leon, 1999;McGoldrick et al, 1999) and as a means for promoting culturally sensitive practice (Carter, 1997;van Wormer, 1999;Zuniga, 1997).…”
Section: The Strengths Perspective and Ngosmentioning
confidence: 99%